Peran Organisasi dan Motivasi Belajar dalam Meningkatkan Prestasi Mahasiswa FE - Nurmaidah Nurmaidah; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This study aims to determine the effect of organizational activeness and learning motivation on the learning achievement of students who are active in organizations at the Faculty of Economics, State University of Jakarta, class of 2021. The method used in this research is a quantitative survey method with a descriptive approach. The population in this study amounted to 152 students. The respondent selection technique used random sampling using the slovin formula so that a sample of 110 students of the Faculty of Economics, State University of Jakarta was obtained. Data collection was carried out through distributing closed questionnaires using a Likert scale of 1-5. The data analysis technique used in this study consists of measurement model analysis, structural model analysis, and direct effect hypothesis testing using the SmartPLS program. Based on the results of the research conducted, the results show that organizational activeness (X1) has a positive and significant effect on learning achievement (Y) with a t-count of 3.943> t-table 1.98 with a significance value of 0.000 <0.05, learning motivation (X2) has a positive and significant effect on learning achievement (Y) with a t-count of 5.677> t-table 1.98 with a significance value of 0.000 <0.05, learning motivation (X3) has a positive and significant effect on learning achievement (Y) with a t-count of 677> t-table 1.98. 677 > t-table 1.98 with a significance value of 0.000 <0.05 and organizational activeness (X1) and learning motivation (X2) together have a positive and significant effect on learning achievement (Y) of 49.3% can be seen through R Square and the remaining 50.7% is explained by other factors or variables.